2018
DOI: 10.1016/j.pmcj.2018.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Attitude estimation for indoor navigation and augmented reality with smartphones

Abstract: We investigate the precision of attitude estimation algorithms in the particular context of pedestrian navigation with commodity smartphones and their inertial/magnetic sensors. We report on an extensive comparison and experimental analysis of existing algorithms. We focus on typical motions of smartphones when carried by pedestrians. We use a precise ground truth obtained from a motion capture system. We test state-of-the-art and built-in attitude estimation techniques with several smartphones, in the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…The microelectromechanical systems-based (MEMS-based) relative localization problem is a recent topic, which has been widely investigated in many areas including robotics and control [1][2][3][4][5][6][7][8], healthcare and rehabilitation [9][10][11], consumer electronics mobile devices [12][13][14], and automated driving and navigation [15][16][17][18], both in industry and in scientific research. Independent from the application, accurate and robust attitude estimation is a crucial task to be solved, especially if the results are to be incorporated into unstable closed-loop systems, such as the control algorithms of mobile robots and unmanned aerial vehicles (UAVs) [1].…”
Section: Survey On Attitude Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…The microelectromechanical systems-based (MEMS-based) relative localization problem is a recent topic, which has been widely investigated in many areas including robotics and control [1][2][3][4][5][6][7][8], healthcare and rehabilitation [9][10][11], consumer electronics mobile devices [12][13][14], and automated driving and navigation [15][16][17][18], both in industry and in scientific research. Independent from the application, accurate and robust attitude estimation is a crucial task to be solved, especially if the results are to be incorporated into unstable closed-loop systems, such as the control algorithms of mobile robots and unmanned aerial vehicles (UAVs) [1].…”
Section: Survey On Attitude Estimationmentioning
confidence: 99%
“…The filter has been improved recently in [7], employing the accelerometer and magnetometer measurements in a gradient descent algorithm to correct the quaternion obtained through the integration of rate measurements. Mahony and Madgwick filters are widely utilized algorithms and their performances have regularly been considered in comparative Sensors 2020, 20, 803 3 of 29 analyses [9,13,15,[31][32][33]. In [34], an adaptive-gain CF was proposed to provide good estimates, even in dynamic or high-frequency situations.…”
mentioning
confidence: 99%
“…During magnetic perturbations, the approach from Martin et al [8] helps to avoid the impact of the measurement on the pitch and roll. In accordance with [10], we can thus consider pitch and roll angles well estimated during all kinds of AR motions. However, the yaw angle remains impacted during magnetic perturbations, the consequence will be a PoI misplaced on the horizon line (P z = 0).…”
Section: Evaluation: a Varying Attitude With A Fixed Positionmentioning
confidence: 85%
“…As a first step, we assume the estimated position perfect ( f pos = 0). The experimental study found in [10] identifies a specific behavior of attitude filters during AR motions. We notice that errors on pitch and roll angles are mainly due to the presence of external accelerations during the estimation phase.…”
Section: Evaluation: a Varying Attitude With A Fixed Positionmentioning
confidence: 87%
See 1 more Smart Citation